Implementation of Puzzle Play in Improving Socioemotional School-Age Deaf Children - Sri Ningsih, Ningning; Nurhayati, Farial; Farida, Ida; Pursitasari, Ita (The Center for Disability Studies and Services Brawijaya University, 2024)
Deaf people are part of children with special needs. Hearing loss in deaf children results in disruption of socio-emotional development. In social interaction, emotional plays an important role in the daily life of children. The socio-emotional development of deaf children can be optimized by playing methods or therapy. Play can help children adapt to the environment, and naturally children like to play. The method used in this study is a quasi-experimental approach with a pre-test-post-test control group design approach. Sampling by purposive sampling, with the number of respondents each 32 respondents in the control and intervention groups. The measuring instrument used is the SDQ (Strengths and Questionnaire) which consists of measuring aspects of emotional and prosocial status. Statistical data analysis using Independent sample t-test. The results showed that there was no effect on the group on emotional status (P=0.18 but there was an effect on prosocial (P=0.01). Recommendations for playing puzzles can be applied in providing nursing care to deaf children at various age levels